ACE Insertion/Deletion Polymorphism (rs4646994) Is Associated With the Increased Risk of Multiple Myeloma - Zmorzynski, Szymon; Szudy-Szczyrek, Aneta; Popek-Marciniec, Sylwia; Korszen-Pilecka, Iwona; Wojcierowska-Litwin, Magdalena; Luterek, Małgorzata; Chocholska, Sylwia; Styk, Wojciech; Swiderska-Kołacz, Grazyna; Januszewska, Joanna; Mielnik, Michal; Hus, Marek; et al. (Frontiers in Oncology, 2019)
Introduction: The insertion (I allele) deletion (D allele) polymorphism of ACE gene (rs4646994) may influence the etiopathogenesis of multiple myeloma (MM). ACE gene is expressed in bone marrow cells and encodes angiotensin converting enzyme (ACE). It converts angiotensin I to active peptide angiotensin II, which stimulates proliferation of hematopoietic stem cells. This suggests possible association of ACE I/D gene polymorphism with MM. The aim of our study was to check possible impact of this polymorphism on risk of development and outcome of MM, as well as, sensitivity to bortezomib in cell cultures derived from MM patients. Objects and Methods: Genomic DNA from 98 newly diagnosed MM patients and 100 healthy blood donors were analyzed by PCR method. Chromosomal aberrations were detected by use of cIg-FISH. In a subgroup of 40 MM patients nucleated bone marrow cells were treated with bortezomib in vitro. Results: The Hardy-Weinberg equilibrium test showed that genotypic frequencies diverged significantly from the equilibrium. The differences between I and D allele frequencies in control and study population were significant (p=0.046). We observed the association between DD genotype and more than 2-fold risk of MM – OR=2.69; p<0.0001. We did not detect any significant differences among studied genotypes regarding clinical and laboratory parameters. Moreover we did not observe the association between survival of MM patients and I/D genotypes. Bortezomib increased number of apoptotic and necrotic cells, but the only statistically significant differences were observed in the number of viable cells at 1nM between ID and DD genotypes (p=0.026). Conclusion: Presented results confirmed the significant relationship between ACE (I/D) polymorphism and risk of MM development. We did not observe the association of ACE I/D polymorphism with disease outcome and bortezomib in vitro sensitivity.